Thermal and Thermomechanical Proceedings 10th Intersociety Conference on Phenomena in Electronics Systems, 2006. ITHERM 2006.
DOI: 10.1109/itherm.2006.1645480
|View full text |Cite
|
Sign up to set email alerts
|

Random network percolation models for particulate thermal interface materials

Abstract: Thermal Interface Materials (TIMs) are widely used in the microelectronics industry to adequately expel the waste heat generated in the chips, by reducing the contact resistance between the chip and the heat sink. A critical need in developing these TIMs is apriori modeling using fundamental physical principles to predict the effect of particle volume fraction and arrangements on effective behavior. Such models will enable one to optimize the structure and arrangement of the material. The existing analytical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 9 publications
(9 reference statements)
1
17
0
Order By: Relevance
“…In a subsequent study [11], we found that the earlier model [2] using a cylindrical region to approximate the thermal transport within the filler particles as being less accurate when the polydispersivity of the particulate system increases. We developed a novel semi-spherical approximation to the conductance of fillers as an alternative to the cylindrical region approximation used in reference [2].…”
Section: Random Network Model Finite Elementmentioning
confidence: 90%
See 3 more Smart Citations
“…In a subsequent study [11], we found that the earlier model [2] using a cylindrical region to approximate the thermal transport within the filler particles as being less accurate when the polydispersivity of the particulate system increases. We developed a novel semi-spherical approximation to the conductance of fillers as an alternative to the cylindrical region approximation used in reference [2].…”
Section: Random Network Model Finite Elementmentioning
confidence: 90%
“…But the classical models are often inaccurate at larger volume fractions (up to 80%) and when SDUWLFOHV DUH LQ ³QHDU SHUFRODWLRQ´ DUUDQJHPHQWV ,Q WKHLU VWXG\ D random network model (RNM [2]) was developed and applied to evaluate the effective thermal conductivity of particulate thermal interface materials. The heat transport between the filler particles ZDV DFFXUDWHO\ FDSWXUHG E\ LPSOHPHQWLQJ %DWFKHORU ¶V [6] estimate of the conductance between two spherical particles in near contact.…”
Section: Random Network Model Finite Elementmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of the present paper is to study the effect of polydispersivity on the effective thermal transport in polymeric composites using a computationally efficient random network model developed earlier by the authors [20,21]. The network model was demonstrated in our prior work to capture accurately (for composites with a very high contrast in the constituent thermal conductivities) the effect of random spatial distribution of the particles as well the constituent thermal conductivities on the effective thermal conductivity of the composite.…”
Section: Introductionmentioning
confidence: 99%